Fire-retardant and fire-barrier poly(vinyl acetate) composites for sealant application (eXPRESS Polymer Letters)
Fire-retardant ceramifying poly(vinyl acetate) (PVAc) sealants have been prepared. The degradation of PVA was integrated with the action of the fire retardants to reduce flammable gases, produce carbonaceous char and convert the fillers into a self-supporting ceramic barrier. PVA is readily degraded by elimination of acetic acid, yielding a char that provides a transitory phase as the filler particles fuse into a ceramic mass. Acetic acid is eliminated at similar temperature to the release of water from magnesium hydroxide fire-retardant, thereby diluting flammable acetic acid. The residual oxide from the fire-retardant filler and structural filler are fused by a flux, zinc borate. The degradative and ceramifying processes were characterised using thermogravimetry, infrared spectroscopy, scanning electron microscopy and ceramic strength. Thermogravimetry of the composites was compared with additive mass loss curves calculated from the components. Deviations between the experimental and additive curves revealed interactions between the components in the composites. The modulus of the PVAc composites and the strength of their ceramic residues after combustion were determined.